Many-Body Effects in a Composite Bosonic Josephson Junction - Sudip Kumar Haldar; Anal Bhowmik (Atoms)
In standard bosonic Josephson junctions (BJJs), particles tunnel between two single-well potentials linked by a finite barrier. The dynamics of standard BJJs have been extensively studied, both at the many-body and mean-field levels of theory. In the present work, we introduce the concept of a composite BJJ. In a composite BJJ, particles tunnel between two double-well potentials linked by a finite potential barrier between them. We focused on the many-body facets of quantum dynamics and investigate how the complex structure of the junction influences the tunneling. Employing the multiconfigurational time-dependent Hartree method for bosons, highly accurate many-boson wavefunctions were obtained, from which properties were computed. We analyzed the dynamics using the survival probability, the degree of fragmentation of the junction, and the fluctuations of the observables, and discuss how the many-boson tunneling behaved, and how it may be controlled, using the composite nature of the junction. A central result of this work relates to the degree of fragmentation of composite BJJs with different numbers of bosons. We provide strong evidence that a universal degree of fragmentation into multiple time-dependent modes takes place. Further applications are briefly discussed.